Toxicological Evaluation of Ginger (Zingiber afficinale) and Kayu Secang (Biancaea sappan) Extracts using Brine Shrimp (Artemia Salina L.) - Giri, Made Kurnia Widiastuti; I Wayan Muderawan (Universitas Pendidikan Ganesha, 2024)
Ginger (Zingiber oficinale) and sappan wood (Biancaeae sappan) are herbaceous plants that are commonly used as herbal decoctions. Due to their wide biological and pharmacological activity, many natural compounds can serve as the foundation for the creation of modern medicines. Some of them are also known to have toxicological characteristics that are important in the development of cancer drugs. Objective: This study aims to evaluate the toxic effects of secang wood extract (Biancaeae sappan) and ginger (Zingiber oficinale) on saltwater shrimp (Artemia salina L.).Methods: The design of this study was a laboratory experimental analysis using the Brine Shrimp (Artemia Salina L.) method. The extract was prepared using standard methods and its toxicity was evaluated using a saltwater shrimp death test. Results: The results of the study were shown by determining its lethal concentration (LC50) which affects 50% of the shrimp population. showed that ginger extract was very toxic to shrimp brine with an LC50 value of 12.91. This shows that both extracts have high toxicity and can have a good effect on cells undergoing carcinogenesis even at relatively low concentrations. Conclusion: These findings highlight the importance of careful use and proper handling of extracts to minimize the potential health risks associated with the toxicity of herbal extracts. Further research is needed to elucidate the specific components responsible for the observed toxicity and to explore the potential use of herbal extracts as anti-cancer and antioxidants.